Androgen-Induced Secondary Hypogonadism and Associated Erectile Dysfunction in Recreational Weightlifters: A Narrative Review - Kravets, Alesia; Zhukava, Lizaveta; Bessmylna, Kateryna; Chrobak, Agata; Alansi, Abdulrahman; Weng, Kai-Chiun; Żukowska, Joanna Katarzyna; Volkava, Darya; Sakovich, Volha; Kacynel, Ewa; et al. (Quality in Sport, 2026)
Background. Anabolic-androgenic steroid (AAS) abuse is extremely common among amateur athletes and bodybuilders seeking to improve their physical appearance and performance. Chronic use of these substances in supraphysiological doses leads to severe suppression of the hypothalamic-pituitary-testicular (HPT) axis, resulting in anabolic steroid-induced hypogonadism (ASIH). Aim. This work aims to summarize the current knowledge and available scientific evidence regarding the effects of AAS abuse on the male reproductive system, with particular emphasis on the mechanisms of secondary hypogonadism and erectile dysfunction in amateur bodybuilders. Material and Methods. A comprehensive review of the medical literature was conducted, including available clinical trials, observational studies, meta-analyses, and case reports of men using or abusing AAS. The analysis assessed hormonal parameters (FSH, LH, total testosterone), semen parameters, sexual function, and the patterns and time to reversal of these changes after steroid discontinuation. Results. Chronic AAS abuse profoundly suppresses the secretion of endogenous gonadotropins (LH and FSH), leading to a drastic decrease in intratesticular testosterone and secondary hypogonadism. Men often report sexual dysfunction, particularly during the withdrawal period (so-called "post-cycle"), with erectile dysfunction and decreased sexual desire observed in between 10% and over 30% of them. Conclusions. Secondary hypogonadism and erectile dysfunction are significant yet underestimated consequences of AAS abuse in amateur bodybuilding. Although hormonal parameters and sexual function return to normal in most patients after discontinuing doping, this process can be lengthy and often requires individualized medical intervention, such as the use of human chorionic gonadotropin (hCG) or selective estrogen receptor modulators (SERMs), to accelerate recovery of the HPG axis.